Bibliotherapy for an adolescent with major depressive disorder, psychotic symptoms, smartphone addiction, and risk of violence: A case study - Dhiky Muhammad Ridwan; Yanuar Fahrizal; Rustini Rustini (JOURNAL OF Mental Health Concerns, 2026)
Background: Major depressive disorder in adolescents is often accompanied by emotional and behavioural problems. Excessive smartphone use may further aggravate these conditions and contribute to behavioural disturbances, including an increased risk of violent behaviour. Purpose: To describe the implementation of bibliotherapy as a non-pharmacological psychiatric nursing intervention for an adolescent with major depressive disorder, psychotic symptoms, a risk of violent behaviour, and high smartphone addiction. Method: This descriptive case study was conducted in Lily 3 Ward of Soerojo Hospital. A 15-year-old adolescent received bibliotherapy as part of comprehensive psychiatric nursing care for seven consecutive days. Baseline emotional and behavioural functioning was assessed using the Strengths and Difficulties Questionnaire (SDQ), while smartphone addiction was evaluated using the Smartphone Addiction Scale (SAS). Results: Baseline SDQ assessment showed normal emotional symptoms (score = 2) and hyperactivity (score = 4), abnormal conduct problems (score = 6) and prosocial behaviour (score = 3), as well as borderline peer problems (score = 4) and total difficulties (score = 16). The baseline SAS score was 104, indicating a high level of smartphone addiction before the nursing intervention. Conclusion: The baseline findings demonstrated emotional and behavioural difficulties, particularly conduct problems, impaired prosocial behaviour, borderline overall difficulties, and high smartphone addiction in an adolescent with major depressive disorder. These findings support the implementation of bibliotherapy as part of comprehensive psychiatric nursing care to address the patient's emotional and behavioural needs. Keywords: Adolescents; Bibliotherapy; Major Depressive Disorder; Risk of Violent Behaviour; Smartphone Addiction.